Multiple Brain Abscesses in a Patient with Myasthenia Gravis – a Case Report - Radzevičiūtė, S.; Liaudanskytė, G.; Baužaitė, I.; Balčiūnienė, N.; Vaitkus, A. (Neurologijos seminarai, 2023)
The frequency of brain abscesses is rising, and they continue to be a potentially fatal infection. It may result from an infection source spreading nearby or over great distances. Additionally, immunocompromised patients – including those who have had immunomodulating treatments – represent a significant risk factor for brain abscesses. The presenting signs of brain abscess are variable and nonspecific. Patients most commonly are presented with headache, fever, altered mental status, focal neurologic symptoms, nausea and vomiting. Healthcare providers must maintain a high degree of clinical suspicion for early diagnosis in immunosuppressed patients because of their diminished capacity to generate a typical immune response, which can make typical infection indications less obvious. Brain imaging is critical to improving the prognosis and is necessary for the diagnosis and treatment of brain abscesses. Magnetic resonance imaging (MRI) remains the preferred radiologic method for diagnosis and differentiation. The proper handling of brain abscess samples is crucial for the correct reporting of microbiological findings. In immunocompetent individuals, the best empirical antibiotic therapy for a community-acquired brain abscess is a combination of metronidazole and a third-generation cephalosporin, whereas, in patients with severe immunodeficiency, trimethoprim-sulfamethoxazole and voriconazole should be added. Still, surgical excision or draining of the abscess is the recommended course of treatment, followed by long-term antibiotics. In this article, we present a patient who was diagnosed with brain abscess and treated non-surgically; as also, a multidisciplinary approach of medical care was followed.
Keywords: brain abscess; immunosuppression; myasthenia gravis